Lactate threshold evaluation in swimmers: The importance of age and method - Nikitakis, I. S.; Toubekis, A. G. (International Journal of Sports Medicine, 2021)
The purpose of the study was to define the most appropriate method for the calculation of the speed corresponding to lactate threshold (sLT) in male swimmers. Eight boys and eight adolescents (age: 11.4±0.5 and 15.8±0.8 years) performed 7×200-m swimming front-crawl and after drawing the speed vs. lactate curve, the sLTs were calculated using five methods: i) the intersection of two linear regression lines, ii) visual inspection, iii) D-max, iv) D-max modified, v) intersection of combined linear and exponential regression lines. All methods were compared to the speed corresponding to maximal lactate steady state (sMLSS). Two to four 30-min efforts of continuous swimming at imposed constant pace were used for sMLSS calculation. In both groups, speed of D-max modified was similar to sMLSS (children, 1.061±0.073 vs. sMLSS: 1.071±0.072 m·s-1; p>0.05; effect size: ES=0.15, small; adolescents, 1.318±0.060 vs. sMLSS: 1.284±0.047 m·s-1; p>0.05; ES=0.64, medium). In adolescents, sLT calculated by intersection of two regression lines and by visual inspection presented medium ES (0.22-0.24) and were no different to sMLSS (1.296 ± 0.051, 1.295±0.053 m·s-1, p>0.05). When testing children, D-max modified is the most appropriate method to estimate sMLSS. The intersection of the linear regression lines and visual inspection are suggested for sMLSS determination in adolescents.